2015
DOI: 10.1002/eat.22396
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in psychosocial impairment associated with eating disorder features in adolescents: A school‐based study

Abstract: There appear to be few differences between male and female adolescents in terms of psychosocial impairment associated with EDF. The findings support the need for preventive interventions that seek to reduce the adverse impact of EDF in both boys and girls. The logistic and policy challenges inherent in such efforts warrant greater consideration. Further research is needed to elucidate the help-seeking behavior of young men with EDF who experience psychosocial impairment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 43 publications
2
42
1
Order By: Relevance
“…We found significant associations between DE and clinical mental health problems and problems with functioning. This is broadly consistent with an Australian study (Bentley et al, ) which found associations between DE and greater psychological distress and poorer quality of life; and with research from America which found a direct relationship between DE and suicidal ideation (Brausch & Gutierrez, ). We also found that adolescents with subclinical DE had three times greater odds of reporting suicidal ideation than adolescents with no DE; the odds were even higher among adolescents with a suspected (12 times greater) or lifetime eating disorder diagnosis (nine times greater); this is the first study to document this association.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…We found significant associations between DE and clinical mental health problems and problems with functioning. This is broadly consistent with an Australian study (Bentley et al, ) which found associations between DE and greater psychological distress and poorer quality of life; and with research from America which found a direct relationship between DE and suicidal ideation (Brausch & Gutierrez, ). We also found that adolescents with subclinical DE had three times greater odds of reporting suicidal ideation than adolescents with no DE; the odds were even higher among adolescents with a suspected (12 times greater) or lifetime eating disorder diagnosis (nine times greater); this is the first study to document this association.…”
Section: Discussionsupporting
confidence: 89%
“…In a longitudinal study of 717 American adolescents, fasting, frequent exercise for weight loss, and self‐induced vomiting were associated with increased risks of mood disorders and suicide attempts (Johnson, Cohen, Kasen, & Brook, ). In a study of 1,749 Australian adolescents (Bentley, Gratwick‐Sarll, Harrison, & Mond, ), binge eating, purging, and excessive exercise were associated with psychological distress and poor quality of life. Findings also suggest varying impacts according to DE severity.…”
Section: Introductionmentioning
confidence: 99%
“…Data for n = 9 participants who were younger than 12 years or older than 18 years of age, n = 70 participants with high levels of missing or corrupt data, and n = 4 participants who did not indicate their gender were excluded. The final sample therefore comprised N = 1666 12–18 year‐old boys ( n = 531; 32%) and girls ( n = 1135; 68.0%) …”
Section: Methodsmentioning
confidence: 99%
“…The final sample therefore comprised N 5 1666 12-18 yearold boys (n 5 531; 32%) and girls (n 5 1135; 68.0%). [24][25][26] Measures Body Image Disturbance. Dissatisfaction, overvaluation, and preoccupation were measured using five items of the Eating Disorder Examination Questionnaire (EDE-Q), 27 a self-report measure of cognitive and behavioral eating disorder features experienced over the past 28 days.…”
Section: Sampling Procedures and Participantsmentioning
confidence: 99%
“…That is, the proportion of men in ED network analysis studies ranges from 0% (Forrest et al, 2018;Olatunji, Levinson, & Calebs, 2018) to a maximum of only 25.8% (Wang et al, in press). Given that males account for up to roughly 20-25% of affected individuals (Hudson, Hiripi, Pope, & Kessler, 2007; Mohler- Kuo, Schnyder, Dermota, Wei, & Milos, 2016;Udo & Grilo, 2018) and that most ED features are associated with similar levels of distress and impairment between males and females (Bentley, Gratwick-Sarll, Harrison, & Mond, 2015;Mitchison, Mond, Slewa-Younan, & Hay, 2013), inadequate samples of males in ED networks is problematic.…”
Section: Intoductionmentioning
confidence: 99%